PENGEMBANGAN PORTAL E-LEARNING GEOGRAFI BERBASIS MOODLE UNTUK MENINGKATKAN KEMAMPUAN NETWORKING DAN SPATIAL ABILITY PESERTA DIDIK DI SMA AL ISLAM 1 SURAKARTA TAHUN 2013/ 2014 - tanwir, muhammad (Pendidikan Geografi, 2013)
PENGEMBANGAN PORTAL E-LEARNING GEOGRAFI BERBASIS MOODLE UNTUK MENINGKATKAN KEMAMPUAN NETWORKING DAN SPATIAL ABILITY PESERTA DIDIK DI SMA AL ISLAM 1 SURAKARTA TAHUN 2013/ 2014 Muhammad Tanwir 1*)Setya Nugraha2)Singgih Prihadi 2) 1) Mahasiswa S1 Pendidikan Geografi FKIP Universitas Sebelas Maret Surakarta2) Dosen Pendidikan Geografi FKIP Universitas Sebelas Maret Surakarta*) E-mail : maspk.glazens@gmail.com ABSTRACTThe purpose of this study were: 1) determine the development of E-Learning Portal Geography Moodle-based learning to enhance the ability of networking and spatial ability learners and 2) determine the effectiveness of the use of E-Learning Portal Geography in learning to improve networking capabilities and spatial ability learners.The researach method used in this research is a method of research and development (R & D). Subjects were media experts, materials experts, educators, and learners. The technique of sampling used is proportional random sampling and data collection instruments using sheet media expert validation, materials specialists, educators, trial questionnaires, observations, pre-test and post-test and documentation.The results of this study are portal-based e-Learning Geography Moodle to enhance the ability of networking and spatial abilities obtain good results and declared unfit for use. The effectiveness of the use of E-Learning Portal-based on Geography Moodle to improve Networking obtain good results measured from the increased active learners in the class of liveliness by 25% (+ 9) of the amount students increased to 58.3% (+ 20 people) and more effective than the use of E-Learning Portal-based Edmodo Geography active learners which improves 38.4% (+ 15 people). Effectiveness of E-Learning Portal-based on Geography Moodle to enhance the Spatial Ability based on Independent Sample T Test shows t arithmetic 5.376 and  t table  1.66 (5% significance level) so it is more effective to use in the learning process.Keywords: E-Learning, Moodle, Spatial Skills